Analysis of Maritime Security Business Safety Construction Business With Analytical Network Process Model - Ade Supandi; Arief Daryanto; Bunasor Sanim; Luky Adrianto ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2020)
The main problem in the shipping industry in Indonesia is the sluggishness of the shipping business due to underconsidered risk management. In the period of 11 years from 2007 to 2018, the problem in this study was how to determine the priority of choices that could be taken into consideration in the shipping industry. The research objective is to get priority actions that can be taken in advancing the shipping industry business. The method used in this study is respondent data collection by data analysis using the Analytic Network Process (ANP). The results of research that discusses how to manage the risk that is at the highest priority with a weight of 0.39092. Next is the process of maintaining business with a priority weight of 0.27899, implementation with a priority weight of 0.18325 and also a low priority management oversight with a priority weight of 0.14684. Future opportunities are to consider and consider risk management arrangements.